2017
DOI: 10.1016/j.ejps.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Sprayable Carbopol hydrogel with soluble beta-1,3/1,6-glucan as an active ingredient for wound healing – Development and in-vivo evaluation

Abstract: Chronic wounds represent a significant health problem worldwide. There is a need for advanced- and cost-efficient wound healing products able to increase patient comfort and reduce the healing time. The aim of this study was to develop a sprayable hydrogel dressing with beta-glucan (βG) as the active ingredient, targeting future application in the treatment of both chronic and burn wounds. The βG was chosen as an active ingredient because of its promising wound healing capabilities, whereas Carbopol 971P NF (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 36 publications
2
32
0
Order By: Relevance
“…The NoβG (βG-free nanofibers) are not expected to improve wound healing to a greater extent. In our previous study [27] we confirmed the healing potential of βG in wound healing, and present results additionally confirm the positive effects of βG in formulation. The improved wound healing in the βG-nanofiber treated groups as compared to the NoβG-nanofiber group seem to be attributed to the increased wound contraction rather than to an increase in the reepithelization ( Figure 7).…”
Section: In Vivo Wound Healing In Diabetic Micesupporting
confidence: 88%
See 2 more Smart Citations
“…The NoβG (βG-free nanofibers) are not expected to improve wound healing to a greater extent. In our previous study [27] we confirmed the healing potential of βG in wound healing, and present results additionally confirm the positive effects of βG in formulation. The improved wound healing in the βG-nanofiber treated groups as compared to the NoβG-nanofiber group seem to be attributed to the increased wound contraction rather than to an increase in the reepithelization ( Figure 7).…”
Section: In Vivo Wound Healing In Diabetic Micesupporting
confidence: 88%
“…In our previous study on wound healing potential of βG formulated as hydrogel, we failed to prove its superiority as wound dressing. We suggested that the failure can be due to an adverse effect of Carbopol 971P NF in the hydrogel formulation [27]. The current in vivo results support the suggested explanation.…”
Section: In Vivo Wound Healing In Diabetic Micesupporting
confidence: 73%
See 1 more Smart Citation
“…8 Recognized as pathogen-associated molecular patterns (PAMPs), b-glucans are a heterogeneous group of polysaccharides that are potent innate immune inducers. 9,10 Through their ability to attract macrophages, neutrophils, and other immune cells, these water-soluble PAMPs fight infections at the wound site, and enhance the migration and proliferation of keratinocytes and fibroblasts, which are critical events in the complicated wound healing process. In addition, b-glucan shows antiinflammatory and antioxidant effects, which are essential for injury healing.…”
Section: Introductionmentioning
confidence: 99%
“…Blending PVA with other polymers enhances the setbacks of PVA hydrogel thereby improving the wound healing process. β-1,6branched-β-1,3-glucan (Beta-glucan), a complex hetero-polysaccharide, is a potent activator of macrophage cells along with inducing the proliferation of dermal cells [15].…”
Section: Introductionmentioning
confidence: 99%